Soil enzyme activities and health indicator characteristics in furrow‐irrigated and flooded rice production systems - Aziz Ahmed; Jim J. Wang; Manoch Kongchum; Dustin L. Harrell; Nutifafa Adotey; Md Ali Haider; Lewis Gaston; Changyoon Jeong (Agrosystems, Geosciences & Environment)
Abstract Conventional delayed‐flood rice (Oryza sativa L.; DFR) cultivation in United States faces increasing challenges such as nutrient losses, water scarcity, and greenhouse gas emissions. Alternative furrow‐irrigated rice (FIR) cultivation is gaining interest for its water use efficiency and production flexibility. Despite FIR's growing adoption, its impacts on soil biological functioning and nutrient cycling remain poorly understood, limiting the ability to optimize management practices for this emerging system. Understanding these impacts is crucial as soil health directly influences nutrient availability, crop productivity, and long‐term sustainability. This study aimed to compare soil enzyme activities and other health indicators between DFR and FIR systems. Soil samples were collected from Louisiana DFR and FIR field experiments established in 2020 and 2021 and analyzed for β‐glucosidase (BG), β‐glucosaminidase (NAG), phosphomonoesterase (PME), arylsulfatase (AST), permanganate oxidizable carbon (POXC), respiration (CO2‐burst), and alkali‐hydrolysable nitrogen (AHN). Principal component analysis (PCA) revealed distinct separations between the DFR and FIR systems in different sites. The results showed that the FIR system significantly (p < 0.05) increased NAG by 35%–57% and AST by 35%–113% activities at both sites as well as BG by 35% and PME by 92% at one of the two site‐years over the DFR system, indicating improved nutrient cycling. The FIR also had significantly (p < 0.05) higher CO2‐burst by 21%–33% and POXC by 44% at one of the two sites than the DFR. Rice grain yields were significantly and positively related to BG (R2 = 0.28, p < 0.05) and PME (R2 = 0.18, p < 0.05) in the FIR system across site‐years but not in the DFR system, reflecting different sensitivities of these enzymes to the two rice cultivations. This study provides insights into understanding the difference in nutrient cycling between the two rice production systems.